Síntese, caracterização e atividade biológica de complexos fosfínicos de rutênio (II) com ligantes CO, NO+, NO2-, NO3-, piridina e 4-picolina - Silva, Henrique Vieira Reis (2016)
A series of ruthenium phosphine/diimine complexes were prepared and characterized as [RuCl(L)(dppb)(4,4`-Mebipy)]PF6 (dppb = 1,4-bis(diphenylphosphino)butane, 4,4`-Mebipy = 4,4'-dimethyl-2,2'-bipyridine and L = CO, NO+, NO2-, NO3- , pyridine and 4- picoline), by IR, UV-Vis, 1H, 31P{1H} and 13C{1H} NMR spectroscopies, elemental analysis, X-ray Powder Diffraction and cyclic voltammetry. In addition, the crystal structure of [RuCl(CO)(dppb)(4,4`-Mebipy)]PF6 was elucidated by single crystal X-ray diffraction analysis. Also, the preliminary in vitro anticancer activity, on hepatocellular carcinoma (HepG2), HSA and DNA binding experiments were evaluated. Human serum albumin binding constants and thermodynamic parameters suggest spontaneous interactions of the complexes with this protein, by van der Waals forces and hydrogen bonding. Spectroscopic titration study indicated that the ctDNA interacts with the complexes are primarily through non-covalent interactions. Additionally, for all compounds their SI are close to 1, indicating a good selectivity.